2000
DOI: 10.2307/2641022
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Growth of the African Dwarf Shrub Indigofera spinosa Following Simulated Herbivory

Abstract: Use of long-term herbivory studies in understanding the effects of livestock grazing on dwarf shrubs of arid zones of Africa is uncommon. Moreover, research has seldom focused on monitoring a 4-5 yr effect of herbivory at the level of individual plants. This study provided information on field-based experiments and simplified statistical modeling to test compensatory growth responses of individuals of the African dwarf shrub Indigofera spinosa in northwestern Kenya. From August 1986 to January 1990, we simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Compensatory growth has also been found in herbs (Whitham et al 1991, Paige 1992, Alados et al 1997, Cebrian et al 1998, Meyer 1998, Lennartsson et al 1998, Paige 1999, shrubs (Oba 1994, Tolvanen and Laine 1997, Oba et al 2000, and trees , Dangerfield and Modukanele 1996, Kudo 1996, Bergströ m et al 2000) (see also review in Strauss and Agrawal 1999). Responses to herbivory may depend on the timing of herbivory, the type and extent of herbivory, the availability of resources in the environment to support regrowth (McNaughton 1983, Rosenthal andKotanen 1994), and the grazing/browsing history of the plant (McNaughton 1983, Paige 1992, Lennartsson et al 1997.…”
mentioning
confidence: 99%
“…Compensatory growth has also been found in herbs (Whitham et al 1991, Paige 1992, Alados et al 1997, Cebrian et al 1998, Meyer 1998, Lennartsson et al 1998, Paige 1999, shrubs (Oba 1994, Tolvanen and Laine 1997, Oba et al 2000, and trees , Dangerfield and Modukanele 1996, Kudo 1996, Bergströ m et al 2000) (see also review in Strauss and Agrawal 1999). Responses to herbivory may depend on the timing of herbivory, the type and extent of herbivory, the availability of resources in the environment to support regrowth (McNaughton 1983, Rosenthal andKotanen 1994), and the grazing/browsing history of the plant (McNaughton 1983, Paige 1992, Lennartsson et al 1997.…”
mentioning
confidence: 99%
“…Therefore, the plant overcompensates for the experienced losses by producing even more flowers (MCNAUGHTON 1983). This mechanism has been demonstrated for other African species, for example the dwarf shrub Indigofera spinosa (OBA et al 2000) and Acacia drepanolobium (GADD et al 2001) and could also apply for D. schoenlandianum which seems to be a palatable species, as its seeds were very frequently found in dung (compare 3.7). However, with higher grazing pressure, the increased production of flowers might be insufficient for overcompensating the more severe losses.…”
Section: Reproductionmentioning
confidence: 77%
“…A number of studies summarized in Nowak and Coldwell (1984) indicated that partial defoliation resulted in increased photosynthetic rates for leaves that remained. Increased plant growth rates have been reported for the African dwarf shrub Indigofera spinosa exposed to different levels of clipping (Oba et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Some plants respond to loss of leaf tissue by increasing growth rates (Oba et al 2000;Verges et al 2008), altering resource allocation patterns (Sun et al 2009), or increasing the photosynthetic rate (Nowak and Coldwell 1984;Meyer 1998). The effects of defoliation and leaf damage on growth characteristics of clonal species have not been studied as extensively as in other species (Esmaeili et al 2009).…”
Section: Introductionmentioning
confidence: 99%